Peak appearance time in pulse waveforms of intracranial pressure and cerebral blood flow velocity - Ziółkowski, Arkadiusz; Pudełko, Agata; Kazimierska, Agnieszka; Uryga, Agnieszka; Czosnyka, Zofia; Kasprowicz, Magdalena; Czosnyka, Marek (Frontiers in Physiology, 2023)
The shape of the pulse waveforms of intracranial pressure (ICP) and cerebral blood flow velocity (CBFV) typically contains three characteristic peaks. It was reported that alterations in cerebral hemodynamics may influence the shape of the pulse waveforms by changing peaks’ configuration. However, the changes in peak appearance time (PAT) in ICP and CBFV pulses are only described superficially. We analyzed retrospectively ICP and CBFV signals recorded in traumatic brain injury patients during decrease in ICP induced by hypocapnia (n = 11) and rise in ICP during episodes of ICP plateau waves (n = 8). All three peaks were manually annotated in over 48 thousand individual pulses. The changes in PAT were compared between periods of vasoconstriction (expected during hypocapnia) and vasodilation (expected during ICP plateau waves) and their corresponding baselines. Correlation coefficient (rS) analysis between mean ICP and mean PATs was performed in each individual recording. Vasodilation prolonged PAT of the first peaks of ICP and CBFV pulses and the third peak of CBFV pulses. It also accelerated PAT of the third peak of ICP pulses. In contrast, vasoconstriction shortened appearance time of the first peaks of ICP and CBFV pulses and the second peak of ICP pulses. Analysis of individual recordings demonstrated positive association between changes in PAT of all three peaks in the CBFV pulse and mean ICP (rS range: 0.32–0.79 for significant correlations). Further study is needed to test whether PAT of the CBFV pulse may serve as an indicator of changes in ICP – this may open a perspective for non-invasive monitoring of alterations in mean ICP.